Tube placement using 'IRIS': A pilot assessment of its utility and safety. (October 2021) - Taylor, Stephen J.; Sayer, Kaylee; Terlevich, Ana; Campbell, David
Abstract: Introduction: Most critically ill patients have a feeding tube placed blindly, but 0.5% result in a major lung complication because misplacement is only detected at the end of procedure. Real-time guided tube placement may pre-empt such complications. This clinical effectiveness study examined the ability to visualise anatomy using Kangaroo™ feeding tubes with IRIS technology ('IRIS' tube). Methods: In a single centre, gastric or intestinal integrated real-time imaging system (IRIS) tubes were prospectively placed in critically ill patients noting the anatomical visualisation. Results: Of 15 placements, 13 were successful gastric placements and used for feeding but one gastric and one intestinal placement failed because of signal loss and inability to find the pylorus, respectively; both tubes were removed. Air insufflation and fluid aspiration were possible with all tubes. Respiratory misplacement was clearly differentiated, prior to reaching the main carina, from gastrointestinal (GI) anatomical markers, permitting removal before causing trauma. Furthermore, non-traumatic placement was visualised in high-risk cases including during advancement through a nostril with a base of skull fracture and into a stomach with a recently haemorrhaging gastric polyp. Individually assessed, direct vision may offer greater safety. X-ray or pH of aspirated fluid confirmed the position of GI tube placements. One adverse event occurred during placement, reversible bradycardia, in a patient previously having bradycardia. Vision was intermittently obscured by bile, mucus or impaction with mucosa. Conclusion: 'IRIS' tubes offer real-time guidance regarding anatomical position. Larger studies are needed to establish the best techniques of deploying this equipment and over-coming the difficulties observed.